ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP BRAND IMAGE DAN PERCEIVED QUALITY SERTA DAMPAKNYA PADA PURCHASE INTENTION (Studi pada Lipstik Sariayu Martha Tilaar di Kota Semarang) - Demante, Karina; Dwiyanto, Bambang Munas (Diponegoro Journal of Management, 2019)
Survived more than 30 years in the Indonesian cosmetics market, but Sariayu Martha Tilaar's lipstick is now experiencing a shift in market position as evidenced by the decline in the Top Brand Index for three years in a row from 2016-2018. This study aims to analyze the effect of electronic word of mouth on brand image and perceived quality and its impact on purchase intention on Sariayu Martha Tilaar lipstick.Non-probability technique was used for sampling with purposive sampling. Data were collected from 148 respondents aged 19-35 who in Semarang and used internet as a source of information for cosmetic products. The analytical method used is the Structural Equation Model (SEM) using Maximum Likelihood technique, which is processed using AMOS version 24.0.The results showed that electronic word of mouth has positive and significant influence on brand image and perceived quality. Perceived quality has positive and significant influence on purchase intention while brand image does not influence purchase intention. Electronic word of mouth also has an indirect influence on purchase intention through perceived quality.